Verapamil Blocks Scopolamine Enhancement Effect on Memory Consolidation in Passive Avoidance Task in Rats - Giménez De Béjar, Verónica; Caballero Bleda, María; Popović, Natalija; Popović, Miroljub (Frontiers in Pharmacology, 2017)
Our recent data have indicated that scopolamine, a nonselective muscarinic receptor antagonist, improves memory consolidation, in a passive avoidance task, tested in rats. It has been found that verapamil, a phenylalkylamine class of the L-type voltage-dependent calcium channel antagonist, inhibits [3H] N-methyl scopolamine binding to M1 muscarinic receptors. However, there are no data about the effect of verapamil on memory consolidation in the passive avoidance task, in rats. The purpose of the present study was to examine the effects of verapamil (0.5, 1.0, 2.5, 5.0, 10 or 20 mg/kg i.p.) as well as the interaction between scopolamine and verapamil on memory consolidation in the step-through passive avoidance task, in Wistar rats. Our results showed that verapamil (1.0 and 2.5 mg/kg) administered immediately after the acquisition task significantly increased the latency of the passive avoidance response, on the 48h retested trial, improving memory consolidation. On the other hand, verapamil in a dose of 5 mg/kg, that per se does not affect memory consolidation, significantly reversed the memory consolidation improvement induced by scopolamine (1 mg/kg, i.p., administered immediately after verapamil treatment) but did not change the passive avoidance response in rats treated by an ineffective dose of scopolamine (30 mg/kg). In conclusion, the present data suggest that 1) the post-training administration of verapamil, dose-dependently, improves the passive avoidance response, 2) verapamil, in ineffective dose, abolished the improvement of memory consolidation effect of scopolamine and 3) exists interaction between cholinergic muscarinic receptors and calcium homeostasis related mechanisms in the consolidation of emotional memory.